Lanskap Pertahanan Militer Jepang Di Jawa - Daya Negri Wijaya; Firza Azzam Fadilla; Gema Budiarto (Badan Riset dan Inovasi Nasional (BRIN), 2026)
This study examines Japan's active military defense system in Java during the Asia-Pacific War period. In addition, this study also aims to analyze and identify the distribution patterns, number, types, and functions of Japanese military defense structures in Java based on Japan's three-layer defense theory. This study used a mixed-methods and historical approach by adapting cultural mapping methods in urban areas. The data collection stages consisted of (1) observation and documentation; (2) interviews; (3) field expeditions; (4) remote geoinformation analysis methods, including the use of satellite imagery and Geographic Information Systems (GIS). This research combined historical sources, quantitative data from GIS geospatial analysis, and qualitative data from observations and interviews. The results of this study have enabled the development of a digital historical map of the Japanese Cultural Heritage Information System in Java. This digital map records the types, functions, numbers, and distribution patterns of Japanese military building remains in Java. A total of 101 military defense building sites have been recorded. Bunker or pillbox defenses were used in coastal and inland defense systems to counter amphibious attacks by Allied forces on the coastline. Meanwhile, natural caves and protective tunnel networks were used as defense systems in forest and hill areas on the island of Java to counter jungle warfare, final defense areas, weapons depots, logistics centers, command centers, medical facilities, and evacuation routes for Japanese military forces.